Answer:
ty I need points your the best
Step-by-step explanation:
.
Answer:
see below
Step-by-step explanation:
The exponent rules that apply are ...
(a^b)(a^c) = a^(b+c)
a^-b = (1/a)^b
(a^b)^c = a^(b·c)
_____
These let you rewrite the given function as ...
f(x) = (3^(2x))(3^1) = 3(3^(2x)) = 3(3^2)^x = 3·9^x
and
f(x) = 3^(2x+1) = (3^-1)^(-(2x+1)) = (1/3)^-(2x+1)
6.6. 2.2*3= 6.6
i hope this makes since
Stairs because they can’t possibly walk up the stairs cause then they’ll fall
You need to add a -1
We can find this by setting up the equation like so
x + (-6) + 12 + 15 / 4 = 5
x + 21 = 20
x = 20 -21
x = -1
Now if we insert -1 where x is located in the equation, you will get a means of 5